PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - I Kadek Yogi Mayudana; Sukendra I Komang (Emasains : Jurnal Edukasi Matematika dan Sains, 2020)
This study aims to determine the increase in mathematics learning outcomes by applying the STAD (Student Teams Achievement Division) cooperative learning model. This type of research is collaborative classroom action research (CAR) designed with two cycles, each cycle consisting of: planning, action, observation, and reflection. The subjects of this study were 39 students of class XII IIS 3 SMA N 7 Denpasar 2017/2018 academic year, and the object of this research was the application of the STAD type cooperative learning model and learning outcomes. The data collection methods are test methods, observation methods, and documentation methods. The results of the research in the first cycle with an average score of student learning outcomes 74.80 and student absorption of 74.80%. In the second cycle the average student learning outcomes 81.92 and 81.92% student absorption. The average percentage of student activities increased by 11.88%. There is an increase in mathematics learning outcomes by applying the STAD cooperative learning model.